THE GENEALOGY OF SOCIAL HISTORY OF ISLAMIC EDUCATION POLITICS IN INDONESIA - Mahfud, Choirul mahfud (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2019)
Studying on the politics of Islamic education in Indonesia cannot be separated from historical aspects. This study discusses why and how the history of Islamic education cannot be separated from the birth, growth and development of Islamic education in a country. In the Indonesian context, the political history of Islamic education cannot be separated from the dynamics of Islamic education and power from time to time, starting from the pre-independence period to the present. This article uses qualitative research methods that emphasize the study of documents or texts. That is, the study of the text in this study focuses more on the analysis or interpretation of written material based on the context. The results of this study indicate that the relationship between history and politics of Islamic education in Indonesia is very close and strong relationship. Azyumardi Azra sees the historical aspect as very dominant in constructing the political reality of Islamic education in Indonesia from time to time. In this context, Michel Foucault gives attention to the genealogical aspects in history which focus on the origin and form of the history of knowledge which in certain contexts cannot be separated from power.